Sociodemographic, Anthropometric, Functional and Psychosocial Factors Associated with Physical Activity in Older Adults - de Sousa B.A.* (2022)
© 2021, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.The practice of physical activity (PA) is an alternative to promote healthy aging. However, the index of physical inactivity of this population is high, being important to investigate factors that can influence this behavior. Thus, this study aimed to analyze associations between PA and sociodemographic, antropometric, functional and psychosocial factors, and to identify the most significant psychosocial predictors for the practice of PA in older adults. A quantitative cross-sectional study was performed with a random sample of 208 older adults (69.9 years ± 6.48 years and 55.3% men). Validated instruments were used to assess PA, functional capacity, self-efficacy, social support and perceived benefits and barriers for PA. There were significant associations between PA and education (r = 0.33), self-efficacy (r = 0.56), social support from friends (r = 0.58) and family (r = 0.25), perceived benefits (r = 0.52) and barriers (r = -0.45). Self-efficacy was the most significant psychosocial predictor for PA in older adults (β = 0.346), followed by perceived barriers (β = 0.152), social support from friends (β = 0.019), perceived benefits (β = 0.118) and social support from family (p = 0.019). This study suggests the importance of psychosocial aspects for the promotion of active aging.